For Indirect Orthodontic Attachment Placement, Adding a Custom Composite Resin Base Is Not Beneficial: A Split-Mouth Randomized Clinical Trial - Mohamed S. Hassan; Fatma A. Abdelsayed; Amany H. Abdelghany; Zac Morse; Mai H. Aboulfotouh (International Journal of Dentistry)
Aim. The aim of this study was to compare the chairside time, bond failure rate, and accuracy of bonding between two orthodontic attachment indirect bonding techniques. Methods and Materials. Two indirect bonding techniques were studied: unaltered base attachment (UA) and custom base attachment (CBA) methods. Eighty-four orthodontic attachments were bonded on six patient stone models. Preoperative models were digitally scanned, and subsequently, attachments were transferred with the aid of a single but sectioned vacuum-formed tray to their corresponding patients. Finally, participants were scanned after attachment bonding to make the postoperative digital replicas. Chairside time and immediate bond failure rates were measured and compared between both techniques. Postoperative and preoperative digital models were then superimposed in order to measure the accuracy of bonding in the three dimensions of space. Results. No differences existed between the two techniques regarding chairside time (P=0.87) and bond failure rates (P=0.37). There were also no differences found for the total attachment movement (P=0.73), mesiodistal (P=0.10), occlusogingival (P=0.31), torquing (P=0.21), and rotational measurements (P=0.18). The UA technique, however, proved to be more accurate for buccopalatal linear directions (P=0.04), whilst the CBA technique showed more accuracy for tipping angular deviations (P<0.01). There was a statistically significant directional bias for the UA towards the occlusal (P<0.01) and palatal (P=0.02) directions with mesial-out angular deviation (P=0.02). Conclusion. The two indirect bonding techniques were comparable for chairside time, bond failure rates, and most linear and angular measurements. The UA technique was, however, superior in buccopalatal directions, while the CBA method showed more tipping accuracy. Both techniques were efficient and reliable for indirect bonding.